(3eYGde GdJfRjd aj GdJaSjQs - (3GdMSjf Hf eSYhO Hf eMeO GdHZhj , GdaqQGA, Ch GHf GdnanqQGA, CHh eMeO, hjdbH HeMjj GdSqfI, (B510 (3g` s ((3ehSi Hf YHO GdebjJs)
(3ChdgG (B:s
(3HYO GdHSedI ; ShQI GdeGFOI eOfjI cdgG EdG bhdg JYGdi Gdjhe CcedJ dce Ojfce ; GdBjI , aEfgG fRdJ HYQaI aj jhe GdLeYI HYO GdYUQs
(3BNQgG (B:s
(3BNQ GdNWGH eY GdfHj Udi Gddg Ydjg hSde hGdeQGO ZjQg hbjd eYfGg dG JLYd CjgG GdEfSGf aJbYO aJHbi ePeheG eNPhdG ePeheG ef ZjQ fUjQ eNPhdG ef ZjQ fUjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 259s
(3eYLe GdeDdajf (B1 / 644s
(3cTa GdXfhf (B2 / 1726s
(3TPQGJ GdPgH (B4 / 48s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs